Intraperitoneal Administration of Silymarin Protects End Organs from Multivisceral Ischemia/Reperfusion Injury in a Rat Model - Aydemir Koçarslan; Sezen Koçarslan; Mehmet Salih Aydin; Şamil Gunay; Mahmut Alp Karahan; Abdullah Taşkın; Murat Üstunel; Nurten Aksoy (Brazilian Journal of Cardiovascular Surgery)
Abstract Objective: To determine whether intraperitoneal silymarin administration has favorable effects on the heart, lungs, kidney, and liver and on oxidative stress in a rat model of supraceliac aorta ischemia/reperfusion injury. Methods: Thirty male Wistar albino rats were divided equally into three groups: sham, control, and silymarin. The control and silymarin groups underwent supraceliac aortic occlusion for 45 min, followed by a 60 min period of reperfusion under terminal anesthesia. In the silymarin group, silymarin was administered intraperitoneally during ischemia at a dose of 200 mg/kg. Rats were euthanized using terminal anesthesia, and blood was collected from the inferior vena cava for total antioxidant capacity, total oxidative status, and oxidative stress index measurement. Lungs, heart, liver and kidney tissues were histologically examined. Results: Ischemia/reperfusion injury significantly increased histopathological damage as well as the total oxidative status and oxidative stress index levels in the blood samples. The silymarin group incurred significantly lesser damage to the lungs, liver and kidneys than the control group, while no differences were observed in the myocardium. Furthermore, the silymarin group had significantly lower total oxidative status and oxidative stress index levels than the control group. Conclusion: Intraperitoneal administration of silymarin reduces oxidative stress and protects the liver, kidney, and lungs from acute supraceliac abdominal aorta ischemia/reperfusion injury in the rat model.